Multimodal Optical Medical Imaging Concepts Based on Optical Coherence Tomography - Leitgeb, Rainer A.; Baumann, Bernhard (Frontiers in Physics, 2018)
Optical medical imaging techniques in general exhibit outstanding resolution and molecule-specific contrast. They come however with a limited penetration in depth and small field of view. Multimodal concepts help to combine complementary strengths of different imaging technologies. The present article reviews the advantages of optical multimodal imaging concepts using optical coherence tomography (OCT) as core technology. In particular we first discuss polarization sensitive OCT, Doppler OCT and OCT angiography, OCT elastography, and spectroscopic OCT as intramodal concepts. To highlight intermodal imaging concepts, we then chose the combination of OCT with photoacoustics, and with non-linear optical microscopy. The selected multimodal concepts and their particular complementary strengths and applications are discussed in detail. The article concludes with notes on standardization of OCT imaging and multimodal extensions.